2021
DOI: 10.1161/strokeaha.120.031709
|View full text |Cite
|
Sign up to set email alerts
|

Trials in Sleep Apnea and Stroke

Abstract: Few randomized controlled trials have evaluated the effectiveness of continuous positive airway pressure (CPAP) in reducing recurrent vascular events and mortality in poststroke obstructive sleep apnea (OSA). To date, results have been mixed, most studies were underpowered and definitive conclusions are not available. Using lessons learned from prior negative trials in stroke, we reappraise prior randomized controlled trials that examined the use of CPAP in treating poststroke OSA and propose the following con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
0
15
0
2
Order By: Relevance
“…In prior studies examining patients with stroke/TIA, expediting diagnosis and treatment of OSA has been shown to improve outcomes. 40 Although all sleep laboratories may not have long wait-times for iPSG, HSAT may also be more convenient and the preferred diagnostic method for patients with stroke/TIA as demonstrated by the number of patients who declined HSAT versus iPSG in our study (9 [7.2%] versus 38 [30.4%], respectively), as well as patients' report of sleep quality that was comparable to sleep at home (89.4% with HSAT versus 31.1% with iPSG). The high rate of patients declining to undergo iPSG highlights stroke/TIA patients' general discomfort and dislike for iPSG, and the need to use better-tolerated ambulatory methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies examining patients with stroke/TIA, expediting diagnosis and treatment of OSA has been shown to improve outcomes. 40 Although all sleep laboratories may not have long wait-times for iPSG, HSAT may also be more convenient and the preferred diagnostic method for patients with stroke/TIA as demonstrated by the number of patients who declined HSAT versus iPSG in our study (9 [7.2%] versus 38 [30.4%], respectively), as well as patients' report of sleep quality that was comparable to sleep at home (89.4% with HSAT versus 31.1% with iPSG). The high rate of patients declining to undergo iPSG highlights stroke/TIA patients' general discomfort and dislike for iPSG, and the need to use better-tolerated ambulatory methods.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies examining patients with stroke/TIA, expediting diagnosis and treatment of OSA has been shown to improve outcomes. 40…”
Section: Discussionmentioning
confidence: 99%
“…Although studies assessing the impact of CPAP on nonvascular outcomes among patients with post-stroke OSA have shown positive outcomes, trials evaluating whether CPAP can reduce the risk of incident stroke or death have been largely negative. 6 The largest of these trials, the Sleep Apnea Cardiovascular Endpoints (SAVE) trial, 7 randomized 2717 patients with coronary or cerebrovascular disease (including 1432 with ischemic stroke or intracerebral hemorrhage) to receive CPAP or usual care. Although the overall findings showed no significant reduction in risk of vascular events or death, a preplanned post hoc subgroup analysis showed that patients who had good adherence to CPAP had a significantly lower risk of cerebrovascular events than those in the usual care group.…”
Section: Commentarymentioning
confidence: 99%
“…Furthermore, in future trials, sample sizes and follow-up periods need to be carefully calculated to assure adequate power and outcome assessment. 6 Investigation of sleep disorders, particularly OSA, should be strongly considered for patients who have had a stroke, with the goal of improving nonvascular outcomes, such as daytime sleepiness, mood and functional outcomes. A good argument can be made for treating OSA like any other vascular risk factor.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation